Integrating Technology Acceptance and Government Trust to Explain Public Engagement on Social Media: An IPMA-Based Study in Local E-Government Communication - Imtihan, Khairul; Rodi, Muhamad; Bagye, Wire; Fitriyani, Baiq Yulia (Depart. of Information Systems, FST, UIN Syarif Hidayatullah Jakarta, 2025)
In the digital transformation era, local governments increasingly use social media to foster transparency, disseminate information, and enhance civic participation. However, challenges remain in ensuring consistent public engagement and user satisfaction, especially in regions with limited digital literacy and uneven access to infrastructure. This study investigates the key determinants of user satisfaction, engagement, and continuance intention in local government social media platforms, with a specific focus on Central Lombok, Indonesia, a rural region facing significant digital inclusion gaps. The research combines the Technology Acceptance Model (TAM), which focuses on how easy and useful a system is, with the e-Government Adoption Model (e-GAM), which looks at factors like trust in the government, transparency, how interactive the platform is, and perceived risks. A survey of 557 users was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) and Importance Performance Map Analysis (IPMA), showing that user satisfaction is greatly affected by how easy the platform is to use and how much users trust it. Digital literacy, interactivity, and institutional trust further shape these perceptions. Interestingly, perceived usefulness and perceived risk did not show strong direct effects, which was surprising and might be due to regular usage habits and dependence on institutional signals in rural areas. IPMA results indicate that interactivity, user trust, and digital literacy are high-impact yet underperforming areas, warranting strategic attention. The study makes progress in theory by merging behavioral and institutional models and provides practical suggestions for improving two-way communication, building public trust, and encouraging digital skill development to boost meaningful participation in local digital governance.